A review on methods of determining onset of asphaltene precipitation - Aboozar Soleymanzadeh; Mohammad Yousefi; Shahin Kord; Omid Mohammadzadeh (Journal of Petroleum Exploration and Production Technology, 2018)
Abstract Oil industry suffers from flow assurance problems that occur both in upstream and downstream operations. One of the common flow assurance issues arises from precipitation and deposition of asphaltenes in various locations along the oil production path including near wellbore region in the reservoir, production tubing, flowlines and separation unit at the surface. Asphaltene particles precipitate out of oil continuum due to changes in temperature, pressure or composition. Such changes in operating conditions occur during different recovery processes (natural depletion, gas injection, chemical injection, etc.) as well as production and blending of different oils during transportation. There are different experimental methodologies documented in the literature that describe how to determine onset of asphaltene precipitation. In this paper, a comprehensive review is performed on all the available procedures to measure onset of asphaltene precipitation. The advantages and limitations associated with all these methods are also documented.